Analysis of Accounting Treatment on Social Responsibility at PT. Angkasa Pura I (Persero) International Airport I Gusti Ngurah Rai- Bali - N W A Sumantini; D P Suciwati; I G M Karma (Journal of Applied Sciences in Accounting, Finance, and Tax, 2018)
Accounting of social responsibility is a useful tool for the company in expressing social activities. This research aims to assess the treatment of social responsibility accounting at PT Angkasa Pura I Bali in accordance with PSAK No. 1 Paragraph 14, law 40 of 2007 and regulation of the minister of SOEs No. PER 02/MBU/7/2017. Technique of collecting data using interview method, observation and documentation. Analysis technique of this research is descriptive qualitative analysis technique and quantitative descriptive analysis technique by using index Wallace. Result of analysis of accountancy treatment of social at PT Angkasa Pura I Bali show accounting treatment of social responsibility has been in accordance with PSAK No.1 Paragraph 14 that has to make a separate report in the Partnership Program and Community Development Report, Main Financial Statements and Sustainability Report. Reporting accounting for socially responsible accountability applied by PT Angkasa Pura I Bali is in conformity with Law 40 of 2007 Article 74 and Regulation of the Minister of SOEs. PER-02/MBU/7/2017 which can be reviewed the form of Partnership Program and Community Development Report consist with guidance on the format of BUMN Minister's Circular Letter no. SE-02/MBU/Wk/ 2012. Social responsibility accounting disclosures presented in the sustainability report at PT. Angkasa Pura I (Persero) based on the GRI G4 guideline produce an index Wallace of 37%.